2021
DOI: 10.3390/su13084399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Public Intentions to Participate in Protection Initiatives for Forested Watershed Areas Using the Theory of Planned Behavior: A Case Study of Cameron Highlands in Pahang, Malaysia

Abstract: The heavy emphasis on land-use changes to meet the needs for gross domestic product growth often causes deforestation, affecting forests’ capability to function as watershed areas properly. While land-use changes generate socioeconomics success, they also lead to environmental deterioration that puts public welfare at greater risk. This study employs the Theory of Planned Behavior (TPB) to evaluate the public’s behavioral intentions towards participation in the protection initiatives for the forested watershed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…TPB is a social psychological theory stating that actual behavior is better predicted by intention or behavioral intent 61 – 64 . As a predictor of actual environmental behavior, intention is a very good indicator 65 67 . According to the TPB, behavioral intention is the strongest direct indicator of actual behavior 65 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…TPB is a social psychological theory stating that actual behavior is better predicted by intention or behavioral intent 61 – 64 . As a predictor of actual environmental behavior, intention is a very good indicator 65 67 . According to the TPB, behavioral intention is the strongest direct indicator of actual behavior 65 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As a predictor of actual environmental behavior, intention is a very good indicator 65 67 . According to the TPB, behavioral intention is the strongest direct indicator of actual behavior 65 . According to this theory, intention refers to the motivation or plan behind an action 68 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the light of considerable research on environmental resource protection, it has been confirmed that those embracing support from families and companions (subjective norms), with a positive attitude (attitude) and believing in one's own ability to participate (perceived behavioral control), were positively and significantly related to behavior intention [18,[22][23][24][25][26]. Therefore, this study hypothesized that residents' subjective norm, attitudes toward conserving urban trees, and perceived behavioral control would have a significant effect on their behavioral intention to pay to conserve urban trees.…”
Section: The Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…There have been many studies using the theory of planned behavior (TPB) developed by Ajzen [21] or using the extended theory of planned behavior (ETPB) by adding in other constructs to analyze different kinds of behaviors or behavioral intentions to conserve environmental resources. With respect to behaviors, in view that most of the actual work is not performed by any resident without qualified professionalism, related studies on resource conservation initiatives tended to conduct surveys mostly on public support, intentions to participate or to pay for the conservation, or willingness to pay (WTP), such as WTP for protecting water resources [22], pay intention for securing the entertainment benefits of an urban forest [23], WTP for protecting urban green space [24,25], support intention of urban tree programs [18] and intention to participate in protection initiatives for forested watershed areas [26].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary medium-sized technology farms are having to deal with a wide array of environmental issues that are a significant source of sustainable production [1][2][3], which comes from the pressure of external stakeholders [4][5][6]. Indeed, external pressures from governments, media, and consumers have also encouraged farm enterprises to adopt new methods to achieve sustainable consumption and production strategies for the environment [7][8][9] because agricultural production has caused great pollution [10][11][12][13]. Therefore, exploring the key variables for environmental innovation (EI) in medium-sized technology farms is crucial, because EI can improve their performance and environmental sustainability [14][15][16].…”
Section: Introductionmentioning
confidence: 99%